2020
DOI: 10.1093/tas/txaa218
|View full text |Cite
|
Sign up to set email alerts
|

Back in the saddle: student response to remote online equine science classes

Abstract: The COVID 19 pandemic has challenged professors and students of all disciplines to adjust quickly to remote online teaching and education platforms. In this new era of remote teaching a greater challenge has been presented in the field of Equine Science; how to effectively share knowledge that is most often demonstrated by providing students access to live, in-person animal examples. Historically, students and teachers believed skill sets which are vital for future careers in the industry (e.g. veterinarian) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
1
0
Order By: Relevance
“…Students reported that these sessions helped them in their exam. They also agreed OL helped them increased interaction even though there were some technical problems 2 Menon et al (2021) [ 51 ] OL; UG medical students from college hospital in South India Online questionnaire Traditional learning ( N = 370) Cross-sectional study The OL barriers reported were connectivity problems, (44.8%) and lack of peer interaction 1 Merson et al (2020) [ 52 ] OL; UG equine science course Online questionnaire Traditional learning ( N = 44) Cross-sectional study Positive feedback on OL, but still, based on Bayesian inference for ANOVA, most of the undergraduates still prefer in-person lessons ( P < 0.05) 1 Muflih et al (2021) [ 53 ] OL; UG health science students from Jordanian universities Online questionnaire Traditional learning ( N = 1210) Cross-sectional study 66.8% agreed that OL made them felt comfortable communicating with their instructors and instructors, 62.6% agreed that the instructor responded quickly to their question. Barriers—75.1% agreed to lack of technical experience, 74.3% lack of experience on online tools, 57.4% lack of motivation, and 62.7% inability to networking 1 Olum et al (2020)[27[ OL; UG medical and nursing students from Makerere University, Uganda Online questionnaire Blended learning ( N = 221) Cross-sectional study Higher interaction (96.3%) in OL.…”
Section: Resultsmentioning
confidence: 99%
“…Students reported that these sessions helped them in their exam. They also agreed OL helped them increased interaction even though there were some technical problems 2 Menon et al (2021) [ 51 ] OL; UG medical students from college hospital in South India Online questionnaire Traditional learning ( N = 370) Cross-sectional study The OL barriers reported were connectivity problems, (44.8%) and lack of peer interaction 1 Merson et al (2020) [ 52 ] OL; UG equine science course Online questionnaire Traditional learning ( N = 44) Cross-sectional study Positive feedback on OL, but still, based on Bayesian inference for ANOVA, most of the undergraduates still prefer in-person lessons ( P < 0.05) 1 Muflih et al (2021) [ 53 ] OL; UG health science students from Jordanian universities Online questionnaire Traditional learning ( N = 1210) Cross-sectional study 66.8% agreed that OL made them felt comfortable communicating with their instructors and instructors, 62.6% agreed that the instructor responded quickly to their question. Barriers—75.1% agreed to lack of technical experience, 74.3% lack of experience on online tools, 57.4% lack of motivation, and 62.7% inability to networking 1 Olum et al (2020)[27[ OL; UG medical and nursing students from Makerere University, Uganda Online questionnaire Blended learning ( N = 221) Cross-sectional study Higher interaction (96.3%) in OL.…”
Section: Resultsmentioning
confidence: 99%
“…Other teaching methods that students found valuable were supplemental reading (x = 1.31; p = 0.05), interactive web-based platforms (x = 1.15), streaming video platforms (x = 1.14), guest speakers (x = 1.13), virtual office hours (x = 1.04), instructor telephone availability (x = 0.90), live chats (x = 0.85), and web conferencing tools (x = 0.75). In similar studies, students found value through guest speakers, interacting with the professor through questions, and supplemental videos greatly beneficial (Merson et al, 2020). Students in equine classes may find additional value in videos where instructors can demonstrate handson skills and students may re-watch the videos to reinforce information.…”
Section: Self-reported Majors Of Students Currently or Previously Enr...mentioning
confidence: 92%
“…These courses often provided equine students with hands-on experiences in the classroom. Teachers and students believe that skill sets vital for future careers in the industry are learned through hands-on experiences (Merson et al, 2020). According to a panel of equine professionals and educators the top five most important skills to be successful in the equine industry included: practice basic barn safety; recognize bad hay/feed; identify unsafe environments; catch, halter, and lead a horse; and provide a physical exam including vital signs.…”
mentioning
confidence: 99%
See 1 more Smart Citation